Family Members as Co-researchers: Reflections on Practice-reported Data - Pål Aarsand (Universitetsforlaget, 2012)
Based on data from two studies, the practice of using participants - here children and parents - as co-researchers to document children's everyday practices is discussed. Participants' video recordings have been analysed from a post-humanistic perspective, in which focus is placed on what kind of data are produced and how this is done within these activities. It is shown how the researcher loses control with regard to understanding how these observations have been made. This raises questions concerning research ethics, as well as the quality of the empirical material that has been collected and that the researcher has to handle. In addition, it is argued that the conditions under which these data are produced demand critical thinking with regard to what analyses can be done.